Effects of inbreeding on performance traits in Karan Fries crossbred cattle - MUMTAZ, SHABAHAT; MUKHERJEE, ANUPAMA; PATHAK, PRAJWALITA; PARVEEN, KAISER (The Indian Journal of Animal Sciences, 2021)
Present study includes the effect of inbreeding on expected genetic gain and estimation of regression with respect to first lactation production, reproduction and lifetime traits in Karan Fries crossbred cattle maintained at ICAR-NDRI, Karnal. Out of total, only 36.97% were found to be inbred with an average inbreeding coefficient 3.68%. Overall least squares mean for reproduction traits (days) AFC, SP, DP and CI were 1020.41 ± 5.49, 141.42± 3.86, 74.54 ± 2.04 and 421.20 ± 3.81 respectively. For production traits (kg) were 305MY, LL, LTMY, FY and SNFY were 3169.15 ± 37.87, 353.25 ± 4.18, 3686.10 ± 55.10, 266.19 ± 4.66 and 127.81 ± 2.26 respectively and lifetime traits like LTMY and stayability were 14588.47 ± 486.09 (kg) and 2444.69 ± 41.26 (days) respectively. Among reproduction traits (days), AFC increased by +3.70, DP +3.66 and CI +68.44 however SP decreased by -0.85 d and production traits (kg), 305MY decreased by -10.2 TMY -16.09, LL -1.23 d, 305FY -1.75, 305SNFY - 0.26, LTMY 202.02 and stayability -17.37 days per unit increase in the inbreeding coefficient. Although there was no inbreeding depression in any of the traits except AFC. The expected genetic gain of AFC increased two folds in IBL2 (Fx >5%) as compared to IBL1 (Fx<5) group that is not desirable, so in future, to maintain the optimum genetic gain we should keep inbreeding at optimum level and so more precise pedigree recording and planned mating strategies should be adopted to avoid inbreeding depression in next generation.